OPTIMALISASI MIXER DAN MAXIJET UNTUK DEVELOPMENT GROUND SUPPORT PADA TAMBANG GRASBERG BLOCK CAVE (GBC) PT.FREEPORT TEMBAGAPURA, PAPUA - Teguh Indra Putra; Yoszi Mingsi Anaperta (Journals Mining Engineering : Bina Tambang, 2018)
Abstract. One of the underground mining areas in PT Freeport Indonesia that uses the collapsing method is the Grasberg Block Cave (GBC).The shotcerete production target per day is 40m³ while the production achieved is 33m³. The method to get the optimization effort is done by checking the multiple regression relationship value of the Equipment Availability relationship to the productivity of the mixer and maxijet tools. From the regression results, it is estimated that the optimal working time to achieve shotcerete productivity target is 40 m³ per day. The results of the analysis show that the optimum conditions m in the Mixer and Maxijet devices the UA and PA values are at least 83% in order to achieve 40m3/day shotcrete production. To achieve UA and PA values of 83% so that the production of 40m3 shotcrete per day is needed, it takes real work 399 minutes to 500 minutes. In the case of repair (repair), to achieve ideal conditions required the addition of working hours to 720 minutes which was initially only 480 minutes. During working hours, the plan is 720 minutes, minimum actual working hours are 500 minutes and maximum standby is 100 minutes.Keywords: Shotcerete, Underground Mining, Productivity, Mixer and Maxijet Tools, Equipment Availability